Systematic impact of institutional pressures on safety climate in the construction industry. (August 2016) - He, Qinghua; Dong, Shuang; Rose, Timothy; Li, Heng; Yin, Qin; Cao, Dongping
Highlights: The organizational management commitment to safety and employee involvement are positively related to all three kinds of institutional pressure. The responsibility perception to safety and health is significantly influenced by coercive and mimetic pressure. No significant effects of coercive and normative pressures on the applicability of safety rules and work practices. The importance of external organizational pressures in improving project safety climate in a systematical view. Abstract: This paper explores how three types of institutional pressure (i.e., coercive, mimetic and normative pressures) systematically impact on the safety climate of construction projects. These impacts are empirically tested by survey data collected from 186 questionnaires of construction companies operating in Shanghai, China. The results, obtained by partial least squares analysis, show that organizational management commitment to safety and employee involvement is positively related to all three institutional pressures, while the perception of responsibility for safety and health is significantly influenced by coercive and mimetic pressure. However, coercive and normative pressures have no significant effect on the applicability of safety rules and work practices, revealing the importance of external organizational pressures in improving project safety climate from a systematic view. The findings also provide insights into the use of institutional forces to facilitate the improvement of safety climate in the construction industry.